Relational legal pluralism and Indigenous legal orders in Canada - McKerracher, Kelty (Global Constitutionalism, 2022)
The survival and resurgence of Indigenous legal orders and constitutional traditions in Canada, as elsewhere, disrupt the normative hegemony of the liberal state and articulate a constitutionalism that accounts for a plurality of laws. How can state and non-state legal orders interact across vastly different normative worlds? How can their interaction address the colonial power imbalance and what role should recognition play in this relationship? This article draws on the work of Ralf Michaels on relational legal pluralism and Aaron Mills on Anishinaabe constitutionalism to explore how a legally plural society must embrace Michaels’ challenge of constitutive external recognition: the idea that legal orders mutually constitute each other through recognition without interfering with each other’s factual status as law. External recognition is consistent with strong legal pluralism and is distinct from recognition within the multicultural liberal state, a form of weak legal pluralism and continued colonialism. Mills’ discussion of treaty, rather than contract, as a foundation for shared political community assists in imagining a constitutionalism with/in Canada in which distinct legal orders can mutually constitute each other without domination. Linkage norms may help to establish reciprocal relations among state law and Indigenous legal orders, and the enactment of such ‘tertiary rules of recognition’ from within Indigenous legal orders may itself shift the balance of power. Faculty Reviewed